2021
DOI: 10.1016/j.amsu.2021.102444
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent plasma as a treatment modality for Coronavirus Disease 2019 in Indonesia: A case reports

Abstract: Introduction and Importance: Coronavirus Disease 2019 (COVID-19) has become a pandemic since the beginning of 2020. COVID-19 is also spreading very rapidly in Indonesia and so far, no definitive therapy has been found. Case presentation We report two cases of confirmed COVID-19 with moderate pneumonia, who received 400 ml of convalescent plasma and showed improvements in clinical, laboratory and radiological examinations. Clinical discussion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Multiple studies have shown that passive antibody transfer has important implications for conferring a state of protective immunity in prophylactic or therapeutic settings ( 120 123 ). This involves the passive transfusion of recombinantly produced antibodies or antibodies from the plasma of convalescent patients to a non-immune person to provide immediate protection against severe SARS-CoV-2 infection ( 111 , 124 ).…”
Section: Clinical Implications Of Antibodies In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have shown that passive antibody transfer has important implications for conferring a state of protective immunity in prophylactic or therapeutic settings ( 120 123 ). This involves the passive transfusion of recombinantly produced antibodies or antibodies from the plasma of convalescent patients to a non-immune person to provide immediate protection against severe SARS-CoV-2 infection ( 111 , 124 ).…”
Section: Clinical Implications Of Antibodies In Covid-19mentioning
confidence: 99%
“…According to a Chinese pilot investigation by Chen et al, transfusion of convalescent sera with NAb titers above 1:640 (in 200ml of plasma) is well tolerated and may improve patient outcomes through neutralizing viremia in severe COVID-19 cases ( 123 ). Whereas a case report from Indonesia recommends that the titer of SARS-CoV-2 NAb should be greater than 1:320 to effectively treat COVID-19 patients ( 120 ). Another recent randomized clinical trial also revealed that the use of high-titer convalescent plasma is beneficial in immunocompromised patients who have not yet had an antibody response ( 122 ).…”
Section: Clinical Implications Of Antibodies In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation